2015
DOI: 10.1371/journal.pone.0125104
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Dependent Phosphate Transporters in Osteoclast Differentiation and Function

Abstract: Osteoclasts are multinucleated bone degrading cells. Phosphate is an important constituent of mineralized bone and released in significant quantities during bone resorption. Molecular contributors to phosphate transport during the resorptive activity of osteoclasts have been controversially discussed. This study aimed at deciphering the role of sodium-dependent phosphate transporters during osteoclast differentiation and bone resorption. Our studies reveal RANKL-induced differential expression of sodium-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…For culture of osteoclast‐like cells, femoral marrow cells were harvested from Memo cKO and control mice, treated with 4OH‐tamoxifen 1 μM (Sigma) and colony stimulating‐factor 1 30 ng/mL (CSF1; PeproTech) for 24 hours, then nonadherent cells were differentiated as described . Differentiation was verified by TRAP activity as described .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For culture of osteoclast‐like cells, femoral marrow cells were harvested from Memo cKO and control mice, treated with 4OH‐tamoxifen 1 μM (Sigma) and colony stimulating‐factor 1 30 ng/mL (CSF1; PeproTech) for 24 hours, then nonadherent cells were differentiated as described . Differentiation was verified by TRAP activity as described .…”
Section: Methodsmentioning
confidence: 99%
“…Differentiation was verified by TRAP activity as described . To determine osteoclast resorptive function, 45 Ca release from calcium phosphate‐coated wells was assessed in 96‐well plates from the fifth to the sixth day of differentiation and normalized by TRAP activity as described …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies had suggested expression also in osteoblasts [101], osteoclasts [50], and odontoblasts [64]; however, the expression in osteoclasts appears to be very low and of little physiological relevance [1] and overall these studies performed in rodents have not been replicated in humans.…”
Section: Normal Physiologymentioning
confidence: 97%